2016
DOI: 10.18632/oncotarget.8683
|View full text |Cite
|
Sign up to set email alerts
|

Defective STAT1 activation associated with impaired IFN-γ production in NK and T lymphocytes from metastatic melanoma patients treated with IL-2

Abstract: High dose (HD) IL-2 therapy has been used for almost two decades as an immunotherapy for metastatic melanoma. IL-2 promotes the proliferation and effector function of T and NK cells through the tyrosine phosphorylation and activation of signal transducer and activator of transcription factors (STAT), especially STAT5. However, whether any defects in STAT activation exist in T and NK lymphocytes from melanoma patients are under debate. Here, we measured the extent of HD IL-2-induced phosphorylation of STAT5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The strength of this relationship may be impacted by the heterogeneity of patient samples as well as the small patient population being assessed. However, similar relationships have been reported in the literature to support causal relationships in assessing lymphocyte dysfunction (35). FIGURE 3 | Expression of extracellular surface receptors differs between cryopreserved PBMCs and whole blood samples.…”
Section: Protocol 3-intracellular Ifnγ Stainingsupporting
confidence: 75%
“…The strength of this relationship may be impacted by the heterogeneity of patient samples as well as the small patient population being assessed. However, similar relationships have been reported in the literature to support causal relationships in assessing lymphocyte dysfunction (35). FIGURE 3 | Expression of extracellular surface receptors differs between cryopreserved PBMCs and whole blood samples.…”
Section: Protocol 3-intracellular Ifnγ Stainingsupporting
confidence: 75%
“…This suggests a novel mechanism by which GLOI depletion restrains tumorigenesis through up-regulation of STAT1. The STAT1 protein, composed of 750 amino acids with a size of 91 kDa, has been classified as a tumor suppressor [31,32,33,34,35,36]. STAT1 is involved in defense against pathogens and inhibition of cell proliferation [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFNγ treatment can modulate the expression of BAF155/SMARCC1 in human astrocytoma cell lines [ 34 ]. NK cells from melanoma patients showed impaired activation of STAT1, a critical molecule in the IFNγ-mediated signaling pathway, after IL2 stimulation [ 35 ]. These previous studies suggest that pro-inflammatory cytokines such as IFNγ from NK cells may enhance Th1-type immune responses via inhibiting SRG3 expression.…”
Section: Discussionmentioning
confidence: 99%